PROSES PEMBUATAN MESIN PENCACAH DAN PEMERAS LIDAH BUAYA UNTUK BAHAN DASAR KOSMETIK DENGAN KAPASITAS 30KG/JAM - Setiawan, Bagus; Sutrisno, Franky; NURDIANA, NURDIANA; Lubis, Zulkifli; Mahyunis, Mahyunis (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2017)
Traditional tools used in Aloe vera squeeze are classified as ineffective if used in medium and large scale processing. While the use of aloe vera as a raw material for a product is quite large, it is necessary to use an aloe vera squeezer that is able to overcome and handle the problem. So with the statement above, a machine that is capable of carrying out the process of curing and squeezing aloe vera for cosmetic ingredients is 30 kg / hour. In the process of making aloe vera machines and squeezing equipment used such as sawing machines, manual plate machines, lathes, welding machines, drilling machines, grinding machines. In the process of making this machine there is the main component workmanship and the processing time, namely the machine frame made of 37